Coexistent diabetes is associated with the presence of adverse phenotypic features in patients with hypertrophic cardiomyopathy. (3rd October 2022) - Jex, N; Chowdhary, A; Thirunavukarasu, S; Procter, H; Sengupta, A; Natarajan, P; Kotha, S; Poenar, A M; Xue, H; Cubbon, R; Kellman, P; Greenwood, J P; et al.
Abstract: Background: Type 2 diabetes mellitus (DM) is associated with worsened clinical outcomes in hypertrophic cardiomyopathy (HCM) patients. The reasons for this adverse prognostic association are incompletely understood. Although distinct entities both HCM and DM share common features of impaired myocardial energetics and coronary microvascular function. Purpose: We sought to test the hypothesis that co-existent diabetes is associated with greater reductions in myocardial energetics and perfusion, and higher scar burden in HCM. Research design and methods: Seventy-five age- and sex-matched participants with concomitant HCM and DM (HCM-DM, n=20), isolated HCM (n=20), isolated DM (n=20) and healthy volunteers (HV, n=15) underwent 31phosphorus magnetic resonance spectroscopy and cardiovascular magnetic resonance imaging. The HCM groups were matched for HCM phenotype. The DM groups were matched for diabetes treatment, duration, HbA1c, body mass index and hypertension comorbidity. Results: ESC sudden cardiac death risk scores were comparable between the HCM groups (HCM: 2.2±1.5%, HCM-DM: 1.9±1.2%; p=NS) and sarcomeric mutations were equally common. HCM-DM had the highest NT-proBNP levels (HV: 42 ng/L [IQR: 35–66], DM: 118 ng/L [IQR: 53–187], HCM: 298 ng/L [IQR: 157–837], HCM-DM: 726 ng/L [IQR: 213–8695]; p<0.0001). Left-ventricular ejection fraction, mass and wall thickness were similar between the HCM groups. HCM-DM displayed a greater degree of fibrosis burden with higher scar percentage, and lower global longitudinal strain compared to the isolated HCM. PCr/ATP was similarly decreased in the HCM-DM and DM (HV: 2.17±0.49, DM: 1.61±0.23, HCM: 1.93±0.38, HCM-DM: 1.54±0.27; p=0.0003). HCM-DM had the lowest stress myocardial blood flow (HV: 2.06±0.42 ml/min/g, DM: 1.78±0.45 ml/min/g, HCM: 1.74±0.44 ml/min/g, HCM-DM: 1.39±0.42 ml/min/g; p=0.004). Conclusions: We show for the first time that HCM patients with DM comorbidity display greater reductions in myocardial energetics, perfusion, contractile function and higher myocardial scar burden and serum NT-proBNP levels compared to patients with isolated HCM despite similar LV mass and wall thickness and presence of sarcomeric mutations. These adverse phenotypic features may be important components of the adverse clinical manifestation attributable to a combined presence of HCM and DM. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Diabetes UK